A total synthesis of sarcandralactone A: a general, concise, RCM enabled approach to lindenanolide sesquiterpenoids. Issue 25 (17th June 2015) - Ramesh, Subburethinam; Mehta, Goverdhan
Graphical abstract: Abstract: A total synthesis of lindenane-type sesquiterpenoid natural product sarcandralactone A and its close sibling 5- epi -shizukanolide has been accomplished through a concise strategy in which a one-pot γ-lactone annulation and a RCM reaction constitute pivotal steps.